2020
DOI: 10.52206/jsmc.2020.10.1.294
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ciprofloxacin and Levofloxacin in treatment of Pseudomonas Aeruginosa infection

Abstract: Background: Pseudomonas aeruginosa is the most troublesome and feared pathogen in medical field. It is the sixth mostcommon cause of hospital-acquired infections and the cause of ventilator-associated pneumonia. The most common multidrugresistantgram-negative pathogen in Ventilated Assisted Patient. In our study in 100 patients culture and sensitivity report only 46%were sensitive to oral treatment while 54% of the pseudomonas were resistant to ciprofloxacin and 34% sensitive and 66%resistant to levofloxacin.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These patients presenting to emergencies complained about waiting time, unmet expectations, and negative interactions with ED staff. Local studies also confirmed that patients often utilized emergency services for non-emergent causes (Ahmed et al, 2018;Baugh et al, 2021;Marco et al, 2021). COVID-19 had a negative effect on the mental health of healthcare workers that included post-traumatic stress, anxiety , acute stress disorder, burnout, sleep problems, insomnia, eating disorders, adjustment disorder, emotional exhaustion, and depressive symptoms (Chatzittofis et al, 2021;Uphoff et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…These patients presenting to emergencies complained about waiting time, unmet expectations, and negative interactions with ED staff. Local studies also confirmed that patients often utilized emergency services for non-emergent causes (Ahmed et al, 2018;Baugh et al, 2021;Marco et al, 2021). COVID-19 had a negative effect on the mental health of healthcare workers that included post-traumatic stress, anxiety , acute stress disorder, burnout, sleep problems, insomnia, eating disorders, adjustment disorder, emotional exhaustion, and depressive symptoms (Chatzittofis et al, 2021;Uphoff et al, 2021).…”
Section: Discussionmentioning
confidence: 82%